The Role of Advance Composite material In Contemporary Buildings - Obasanjo Owoyale Adeola; Mohammed Tauheed Alfa (Journal of Contemporary Urban Affairs, 2018)
Composite materials have been used from the earliest times, from wood, which is a naturally occurring composite of lignin and cellulose, through straw reinforced clay bricks to reinforced concrete. In the 20th century, a new breed of composite materials was developed using polymer matrices with high-performance reinforcement fibres. The great effect and uncompromising properties of advance composite materials have enabled the emergence of composites cut across all fields of application and all areas of work, just to mention a few aeronautic engineering, automobile engineering, and medicine, military and building construction. Therefore, with emphasis on building construction, advance composite material has played a vital role in today’s contemporary building construction method, by presenting its self as an alternative building construction material, its application has made the contemporary building construction much more flexible and achievable, compared to traditional building materials and its methods of construction. It further offers the building construction industry the technical know-how of having new possibilities of design styles, shapes and forms. Therefore, advance composite material proves it’s self to be a better and a new alternative building construction material that remains construction friendly and flexible based on its properties. This study, therefore, tends to provide an overview of advance composite material, its application as well as its role in today’s contemporary building.